The Tbr2 Molecular Network Controls Cortical Neuronal Differentiation Through Complementary Genetic and Epigenetic Pathways. (6th September 2016) - Sessa, Alessandro; Ciabatti, Ernesto; Drechsel, Daniela; Massimino, Luca; Colasante, Gaia; Giannelli, Serena; Satoh, Takashi; Akira, Shizuo; Guillemot, Francois; Broccoli, Vania
Abstract: The T-box containing Tbr2 gene encodes for a transcription factor essential for the specification of the intermediate neural progenitors (INPs) originating the excitatory neurons of the cerebral cortex. However, its overall mechanism of action, direct target genes and cofactors remain unknown. Herein, we carried out global gene expression profiling combined with genome-wide binding site identification to determine the molecular pathways regulated by TBR2 in INPs. This analysis led to the identification of novel protein–protein interactions that control multiple features of INPs including cell-type identity, morphology, proliferation and migration dynamics. In particular, NEUROG2 and JMJD3 were found to associate with TBR2 revealing unexplored TBR2-dependent mechanisms. These interactions can explain, at least in part, the role of this transcription factor in the implementation of the molecular program controlling developmental milestones during corticogenesis. These data identify TBR2 as a major determinant of the INP-specific traits by regulating both genetic and epigenetic pathways.